A shadow in Moscow : a Cold War novel - Reay, Katherine, 1970- (A Cold War novel, 2023)
"Two courageous female spies, one with MI6 and the other with CIA during the Cold War in Moscow, must work together before the KGB closes in and destroys them both"--